Molecular Analysis of Rabi Sorghum Genotypes Differing in Osmolytes Accumulation under Water Stress - Damame, S. V.; Naik, R. M.; Chimote, V. P.; Munjal, S. V. (International Journal of Bio-resource and Stress Management, 2016)
Forty-eight sorghum accessions were screened for proline and glycine betaine osmolyte accumulation levels under-0.5 MPa PEG–6000 induced osmotic stress in the leaves of ten days old seedlings. Proline as well as glycine betaine accumulation was higher in stressed than unstressed condition. Under stressed conditions, tolerant sorghum genotypes exhibited highest increase in both the osmolytes, followed by stay-green and susceptible ones. Four each of drought susceptible, tolerant and stay-green sorghum genotypes differing in proline and glycine betaine accumulation potential under osmotic stress were analyzed with randomly amplified polymorphic DNA markers with a view to understand genetic diversity among the different types as well as proline and glycine betaine accumulation potential under water stress. Out of 43 primers screened, 26 amplified genomic DNA with 258 loci of which, 191 were polymorphic with 75.55% polymorphism. Among the random operon primers, thirteen showed twenty unique loci. The Dice similarity coefficient values based on RAPD data ranged from 0.70 to 0.91 with the minimum in a drought susceptible genotype RSV-1006 and the maximum in stay-green genotype M-35-1.The dendrogram revealed a separate major cluster of stay-green genotype, E-36-1. 2D scatter plot showed a separate group of all four stay-green genotypes closely placed with two high proline accumulating tolerant genotypes, RSLG-262 and RSV-1366. However, two high glycine betaine accumulating tolerant genotypes, RSV-458 and Hadgaon local, appeared to be distinct from the stay-green genotypes.